Innovations in Derivatives Markets: Fixed Income Modeling, Valuation Adjustments, Risk Management, and Regulation - Glau, Kathrin; Grbac, Zorana; Scherer, Matthias; Zagst, Rudi; Glau, Kathrin; Grbac, Zorana; Scherer, Matthias; Zagst, Rudi (Cham Springer Nature, 2016)
Quantitative Finance; Banking; Statistics for Business/Economics/Mathematical Finance/Insurance; Mathematical Modelling and Industrial Mathematics; Probability Theory and Stochastic Processes; Financial Engineering
English
Keywords: Food manufacturing & related industries; Engineering: general; Biochemical engineering; Coins, banknotes, medals, seals (numismatics); Quantitative Finance; Banking; Statistics for Business/Economics/Mathematical Finance/Insurance; Mathematical Modelling and Industrial Mathematics; Probability Theory and Stochastic Processes; Financial Engineering